Microbial Growth, Acidification Properties and Formation of Metabolites in Fermented Milk Products Using Various Starter Culture Combinations - Aghlara, Arezou (2008)
The present study investigated the microbial growth, acidification properties and changes in key metabolite compounds during fermentation of sterilized reconstituted skim milk. Fermentation was performed by using single and mixed cultures of Lactobacillus acidophilus LA5 (probiotic strain; A), L. delbrueckii subsp. bulgaricus LB12 (B), Streptococcus thermophilus TH4 (T) and Kluyveromyces marxianus subsp. marxianus LAF4 (M). Fermentation time, lag time and final titratable acidity ranged from 225 to 721 min, 2 to 31 min and 0.76 to 1.25 % (w/v) lactic acid, respectively. At the end of fermentation, the highest counts of L. acidophilus LA5, L. delbrueckii subsp. bulgaricus LB12, S. thermophilus TH4 and K. marxianus subsp. marxianus LAF4 were 8.42, 8.56, 8.91 and 8.69 log10 cfu mL-1, respectively. In all single and mixed cultures containing L. acidophilus LA5, the viable probiotic cell count met the minimum proposed effective level required to observe a positive health effect. In this study, product fermented with traditional yoghurt culture (mixed culture of L. delbrueckii subsp. bulgaricus LB12 and S. thermophilus TH4) showed the highest titratable acidity and the lowest pH during entire storage period. The most stable product in terms of the changing in titratable acidity during storage period was prepared with single culture of S. thermophilus TH4. However, this strain was found likely the responsible of post-acidification when incorporated into the mixed cultures. Viable counts of all lactic acid bacteria and yeast in single and mixed cultures always remained higher than 7 log10 cfu mL-1, however, fluctuation in their counts was observed during 4 weeks of refrigerated storage. Changes in lactose and total glucose and galactose were monitored during fermentation and cold storage by using high performance liquid chromatography (HPLC) coupled to refractive index (RI) detector. Lactose was utilized by all starter culture combinations during fermentation and storage time. The consumption of lactose during fermentation and storage was significantly (P < 0.05) higher in single culture of K. marxianus subsp. marxianus LAF4. The data obtained in this study showed that the changes in total content of glucose and galactose was not paralleled with the changes in lactose content during fermentation and storage. Changes in concentration of citric, orotic, pyruvic, succinic, lactic, formic, acetic, uric, propionic, butyric and hippuric acids was carried out using HPLC coupled to ultraviolet (UV) detector. In general, variable amount of each organic acid was formed with different starter culture used in this study during fermentation process and storage. However, lactic acid was found to be the most abundant organic acid in majority of the products at the end of fermentation and throughout the storage time. The final concentration of lactic acid at the end of fermentation was ranged between 1167 and 8895 mg L-1. The most prominent organic acid in products fermented with single culture of L. delbrueckii subsp. bulgaricus LB12 and mixed culture of L. delbrueckii subsp. bulgaricus LB12 and K. marxianus subsp. marxianus was acetic and citric acid, respectively, followed by lactic acid. Forty volatile compounds were detected using gas chromatography coupled to time-of-flight mass spectrometer (GC-TOFMS). The representative of the alcohols (i.e. ethanol), ketones (i.e. ethyl acetate and ethyl butyrate), esters (i.e. 2-butanone, acetone, 3-hydroxy-2-butanone or acetoin and 2,3-butanedione or diacetyl) and aldehydes (i.e. acetaldehyde) were considered for further analysis. The release of the corresponding volatile flavor compounds into the headspace was monitored during fermentation and 4 weeks of refrigerate storage, using GC coupled to flame ionization detector (FID). In fermented products devoid of K. marxianus subsp. marxianus LAF4, acetoin was seen to be the most prominent volatile flavor substance at the end of fermentation, ranging from 59.5 to 104.2 mg L-1. While, in those co-inoculated with the yeast strain ethanol was observed to be the most abundant volatile flavor compound ranged between 964 and 6522 mg L-1.